Respuesta :

Answer:

E + F = 2c² + 5c + 4

Step-by-step explanation:

[tex]E = 6c^2 - 2c - 1 \\\\F = -4c^2 + 7c +5\\\\E + F = (6c^2 - 2 c -1) + ( -4c^2 + 7c +5)[/tex]

         [tex]=(6c^2 -4c^2) +(-2c + 7c) + (-1 + 5)[/tex]      [tex][\ arranging \ terms\ ][/tex]

         [tex]= 2c^2 + 5c + 4[/tex]

___________________________________

Let's Solve it!

Given that:

[tex]\quad\quad\quad\quad\tt{E = 6 {c}^{2} - 2c - 1}[/tex]

[tex]\quad\quad\quad\quad\tt{ F = - 4 {c}^{2} + 7c + 5}[/tex]

Formula:

[tex]\quad\quad\quad\quad\tt{E + F = ?}[/tex]

Solution:

[tex]\quad\quad\quad\tt{(6 {c}^{2} - 2c - 1) + ( - 4 {c}^{2} + 7c + 5)}[/tex]

Step by step:

[tex] \quad\quad\quad\quad\tt{ ⟶(6 {c}^{2} ) + ( - 4 {c}^{2}) = \boxed{ \pink{2 {c}^{2} }}}[/tex]

[tex] \quad\quad\quad\quad\tt{ ⟶ ( - 2c) + ( 7c) = \boxed{ \pink{5c }}}[/tex]

[tex] \quad\quad\quad\quad\tt{ ⟶ ( - 1) + ( 5) = \boxed{ \pink{4 }}}[/tex]

Now, it will look like this:

[tex] \quad\quad\quad\quad\tt{E + F =2 {c}^{2} + 5c + 4 }[/tex]

So, E + F is equal to:

[tex] \quad\quad\quad\quad\tt{\boxed{ \boxed{ \color{magenta}{ 2 {c}^{2} + 5c + 4 }}}}[/tex]

___________________________________

#CarryOnLearning

✍︎ C.Rose❀

Ver imagen Аноним